Cosmopolitan beginnings? Transnational healthcare workers and the politics of carework in Singapore. Issue 3 (2nd May 2014) - Yeoh, Brenda S A; Huang, Shirlena
<x xml:space="preserve">Abstract</x> In recent times, the increasing scholarly interest in the contested place of the migrant in the cities of the North and South has drawn mainly on frameworks of integration, multiculturalism and cosmopolitanism. Much of the literature pays little heed to gender dynamics and accords little value in particular to the roles that female migrants play in actively shaping the urban contexts in which they live. We contend that by shifting attention to the more feminised spheres oriented towards the private sphere away from public display (including that of 'carework' which is increasingly performed by female migrant workers), we may be able to better glimpse cosmopolitanism at work. This is because the social relations of care provide more fertile ground for developing what Glick Schiller et al. (2011, Ethnic and Racial Studies 34 399–418) call 'cosmopolitan sociability'. This is not to negate the findings of feminist analyses that suggest that carework, particularly in globalising cities restructured by neoliberal agendas, reproduces and extends forms of social inequalities. Indeed, even as the locus of carework shifts from local to foreign women from less developed countries, patriarchal norms and unequal gender relations are reinforced, and in fact intersect with other power geometries based on race, nationality and class. As illustration of the politics of carework, this paper discusses the place of migrant healthcare workers (primarily Chinese, Indian, Filipino and Burmese women) in institutionalised settings in the rapidly globalising city of Singapore. While their presence in the global city raises moral anxieties not only about the shift of carework from the family to outside the home, they also alert us to the possibilities and limits of a cosmopolitan approach to care transcending boundaries of race, culture, language and nationality.